Large Animal Models of Heart Failure With Reduced Ejection Fraction (HFrEF) - Spannbauer, Andreas; Traxler, Denise; Zlabinger, Katrin; Gugerell, Alfred; Winkler, Johannes; Mester-Tonczar, Julia; Lukovic, Dominika; Müller, Claudia; Riesenhuber, Martin; Pavo, Noemi; Gyöngyösi, Mariann (Frontiers in Cardiovascular Medicine, 2019)
Heart failure with reduced ejection fraction (HFrEF) is defined by an ejection fraction (EF) below 40%. Many distinct disease processes culminate in HFrEF, among them acute and chronic ischemia, pressure overload, volume overload, cytotoxic medication and arrhythmia. To study these different etiologies the development of accurate animal models is vital. While small animal models are generally cheaper, allow for larger sample sizes and offer a greater variety of transgenic models, they have important limitations in the context of HFrEF research. Small mammals have much higher heart rates and distinc ion channels. They also have much higher basal metabolic rates and their physiology in many ways does not reflect that of humans. The size of their organs also puts practical constraints on experiments. Therefore, large animal models have been developed to accurately simulate human HFrEF. This review aims to give a short overview of the currently established large animal models of HFrEF. The main animal models discussed are dogs, pigs and sheep. Furthermore, multiple approaches for modeling the different etiologies of HF are discussed, namely models of acute and chronic ischemia, pressure overload, volume overload as well as cytotoxic and tachycardic pacing approaches.